EFFECT OF CHRONIC POLYPHARMACY AND THE DRUG BURDEN INDEX (DBI) ON MUSCLE FUNCTION AND STRUCTURE IN AGED MICE. (11th November 2018) - Gemikonakli, G; Mach, J; Tran, T; Howlett, S; deCabo, R; Le Couteur, D; Hilmer, S
Abstract: Ageing, polypharmacy (≥ 5 different drugs) and increasing DBI (anticholinergic/sedative medication exposure) are associated with falls and impaired physical function. Preclinical ageing models can assess underlying mechanistic changes. We investigated whether chronic therapeutic drugs (polypharmacy or monotherapy), with increasing DBI and/or ceasation (deprescribing), affected physical function and/or muscle histology in mice. 12-month-old male C57BL/6 mice received either control diet or study drug(s). Polypharmacy diets consisted of Zero DBI (metoprolol, simvastatin, omeprazole, paracetamol, irbesartan), Low DBI (metoprolol, simvastatin, omeprazole, paracetamol, citalopram) and High DBI (metoprolol, simvastatin, citalopram, oxycodone, oxybutynin). Individual drugs (High DBI regimen) were tested as monotherapy. At 21-months, animals were randomised to continue treatment or gradual withdrawal. Rotarod performance was assessed at 12-24-months, and balance beam (6mm) at 24-months. Gastrocnemius muscle samples were collected at 27-months. Rotarod results indicate significant reduced endurance for citalopram mice (n=15–36) compared to control (n=24–29; p<0.05) at all time-points, and deprescribing (n=12) improved performance. Compared to control (n=24), balance assessment showed a trend towards impaired performance in High-DBI (n=18; p=0.061) and citalopram (n=14; p=0.134). Compared to metoprolol mice (n=16), metoprolol-deprescribed mice (n=16) showed higher coordination (p=0.016). Preliminary histology results suggest a trend towards less muscle fibres per field in control (n=3), compared to High-DBI (n=3; p=0.119) and citalopram animals (n=2; p=0.049). Our preclinical results suggest High DBI, citalopram and metoprolol drug regimens impact measures of muscle function and structure. Future research will continue to characterise histological changes in muscle including fibre size and types.